(untitled) (Bulletin of criminological association of Ukraine, 2024)
The article is devoted to the analysis of victimogenic factors of the crime of aggression against Ukraine. The external-colonial (historically and geographically determined relations between Russia and Ukraine) and the internal contour of victimization factors have been established, given a description and explanation. In the structure of the latter, the destructive role of strategic deficiencies in the arms control system is emphasized: excessive and uncontrolled sale of arms, unjustified write-offs, embezzlement; anti-state actions with a mobilization reserve; crime in the defense-industrial complex; oligarchization The description of the external (international) contour of victimogenic factors is provided: strategic underestimation of the scale of expansionist claims of the Russian Federation and the degree of military threats; shortcomings of coalition actions after 2014 and, to a greater extent, after February 24, 2022.